(untitled) (Tempo e Argumento, 2025)
This paper takes as its starting point the memoirs of two counterfeiters, produced in interaction with journalists during the first half of the twentieth century. In an era marked by the widespread adoption of writing practices, the rise of detective novels, and narratives of itinerant criminals, these biographies should be read in light of a reading experience that intertwined anxieties about the boundaries between truth and falsehood with a fascination for long-distance travel. Published in the cities of Mexico and Rio de Janeiro, these memoirs offered accounts of a world connected by transatlantic ships, telegraph lines, and the circulation of information, goods, and people. They were, however, marked by a fundamental paradox. These were narratives about subjects in motion, produced by narrators confined within the restricted space of prison